Elymus repens biomass allocation and acquisition as affected by light and nutrient supply and companion crop competition. (26th December 2016) - Ringselle, Björn; Prieto-Ruiz, Inés; Andersson, Lars; Aronsson, Helena; Bergkvist, Göran
Abstract : Background and Aims Competitive crops are a central component of resource-efficient weed control, especially for problematic perennial weeds such as Elymus repens . Competition not only reduces total weed biomass, but denial of resources can also change the allocation pattern – potentially away from the underground storage organs that make perennial weeds difficult to control. Thus, the competition mode of crops may be an important component in the design of resource-efficient cropping systems. Our aim was to determine how competition from companion crops with different modes of competition affect E. repens biomass acquisition and allocation and discuss that in relation to how E. repens responds to different levels of light and nutrient supply. Methods Greenhouse experiments were conducted with E. repens growing in interspecific competition with increasing density of perennial ryegrass or red clover, or growing at three levels of both light and nutrient supply. Key Results Elymus repens total biomass decreased with increasing biomass of the companion crop and the rate of decrease was higher with red clover than with perennial ryegrass, particularly for E. repens rhizome biomass. A reduced nutrient supply shifted E. repens allocation towards below-ground biomass while a reduced light supply shifted it towards shoot biomass. Red clover caused no change in E. repens allocation pattern, while ryegrass mostly shifted the allocation towards below-ground biomass, but the change was not correlated with ryegrass biomass. Conclusions The companion crop mode of competition influences both the suppression rate of E. repens biomass acquisition and the likelihood of shifts in E. repens biomass allocation.